Physical meat quality comparison of selected KUB chicken, original Kampung and improved Kampung chicken with in ovo feeding technology. Issue 1 (June 2021) - Saifullah, S; Dagong, M I A; Pakiding, W
Abstract: The purpose of this study was to determine the comparison of the quality of native chicken meat. The study used 90 Day old chicken (DOC) three types of native chickens. Chickens were reared for 70 days with ad libitum feeding and drinking water. The method used was a completely randomized design (CRD) with 3 treatments and 15 replications. The treatments were P1 (native native chicken, Balitnak superior (KUB)), P2 (ordinary native chicken) and P3 (native chicken in ovo feeding breeds). The parameters measured were the pH value of the meat, water binding capacity, cooking losses, tenderness, and meat color. Research data obtained at pH values P1 (5.92), P2 (5.95), P3 (5.58); water holding capacity (%) P1 (42.6), P2 (37.27), P3 (5.58); cooking losses (%) P1 (18.46), P2 (19.46), P3 (24.86), tenderness (kg/cm 2 ) P1 (0.74), P2 (0.76), P3 (0.94); flesh color L P1 (56.04), P2 (56.60), P3 (54.04), meat color a P1 (5.91), P2 (5.93), P3 (3.82); and meat color b P1 (5.93), P2 (5.98), P3 (5.45). The results showed that although there were differences in pH, water holding capacity, and cooking losses in all treatments, the three of them were still of good quality meat because they had pH values that were still in the normal range and the meat was very tender.